Artificial intelligence techniques in science research and education - Zhang, Shouwen (2009)
The following gives an overview of AI techniques and processes: $$ DATA MINING: The process of extracting previously unknown information from existing data, often with the help of another AI program, using statistical and visualization techniques to discover and present knowledge in a form that is easily comprehensible to humans. Also known as Knowledge Discovery.